Impact of the Tokyo 2020 Olympic Games on Japan’s Economy and Capital Market - Anusha, Annathurai (2021)
This study analyses the impact created by Tokyo 2020 Olympic Games on Japan’s Economy and Capital Market. In this research, the influence of hosting Tokyo 2020 Olympic Games during COVID 19 on Japan’s economy and capital Market as of before and after the event is observed and studied. Event study and GARCH analysis is key methodology used to run and examine this research. Performance of Japan’s economy and capital market that was measured in terms of performance of capital market, investment market and sectoral market by the indexes of TOPIX, Stock Market, Bond Market, Foreign Exchange, FTSE, MSCI, and sectoral index of Air Transportation, Construction, Pharmaceutical shows different range of fluctuation. Japan’s Stock Market Index and Air Transportation Sectoral Index marks greatest Cumulative Abnormal Return after the event date which indicates hosting Tokyo 2020 Olympic Game during COVID 19 has impacted Japan in positive way as of after the event. The nobility of this research is that it gives idea to future researchers on hosting country of any international events on conducting Event study and GARCH analysis to study the key performance of market that will be impacted and further implement pre-event and post-event policy.